Suicidal ideation in the perinatal period: findings from the Thailand–Myanmar border - Fellmeth, G; Nosten, S; Khirikoekkong, N; Oo, MM; Gilder, ME; Plugge, E; Fazel, M; Fitzpatrick, R; McGready, R (Oxford University Press, 2021)
Background Suicide is a leading cause of maternal death globally. Migrant and refugee populations may experience higher risk of suicide. We report data on suicidal ideation from migrant and refugee women living on the Thailand–Myanmar border.